مشتقات "الصرخ" في النسق القرآني: دراسة سياقية:محاولة لبناء منهجية تكاملية لتحليل المشتقات ذات الأصل الواحد في النسق القرآني - معوض، أحمد عبدالموجود عطية سليمان (جامعة الأزهر - کلیة الدراسات الإسلامیة والعربیة للبنات بالقاهرة, 2020)
يأتي هذا البحث في مصاف الدراسات التي تعني بتحليل المشتقات ذات الأصل الواحد في السياقات القرآنية؛ إسهاما في إظهار الدلالات الدقيقة لمفردات القرآن بمنهجية حديثة تقوم على تصور متماسك ومنطقي في فهم النص القرآني. وإنما كانت نظرية السياق بجناحيها الخارجي والداخلي مرتكزا أساسيا قام عليه البحث؛ لأنها تستعمل كل الأدوات التي تفضي إلى فقه المعنى واستكشافه داخل النص بدءا من أصغر وحدة في النص وهي الصوت، ومرورا بالوحدة الصغرى وهي الكلمة، وانتهاء بالوحدة الكبرى وهي الجملة في نسق النص القرآني؛ لذا غدت نظرية السياق في ميدان علم لغة النص نظرية تكاملية بكل ما تعنيه الكلمة. ولأن البحث يهدف إلى تأسيس منهج تحليلي تكاملي يمكن البناء عليه عند دراسة المشتقات ذات الأصل الواحد في إطار النص القرآني، فقد اقتضت طبيعة الموضوع وأهدافه اتخاذ المنهج الوصفي التحليلي طريقا تمضي الدراسة عليه، مع الاستئناس أحيانا بآلية الإحصاء وتحليل النتائج، وقد طبقت هذا المنهج مع كل موضع بأن حددت السياق الخارجي أولا للمقطع القرآني قبل الولوج إلى التحليل اللغوي الذي مر بمراحل تبدأ من التحليل التركيبي للجملة موضع الشاهد وعلاقاتها السياقية مع البنى الأخرى في المقطع، ثم التحليل المورفولوجي لكل كلمة من كلمات الجملة موضع الشاهد وتحديد وظائف مورفيماتها، وأخيرا التحليل الصوتي على المستويين الفوناتيكي والفونولوجي. وقد أثمر اتباع المنهج السابق نتائج منها: أن الأصل الثلاثي لمادة (ص ر خ) مبني في حقيقته الوضعية حول معنى الصوت مطلقا والصياح خاصة، ودلت تقلباته الاشتقاقية حول معنيين متقابلين هما: الإغاثة والاستغاثة، ولم يخل سياق الموقف وجوه في المواضع الأربعة من الفزع والترويع والتحذير والتهديد المشوب بالخوف والقلق وغيرها من المعاني المسببة للصياح والصراخ.
This research comes among the best studies that are meant to analyze the one-root derivative in the Qur'anic contexts. It contributes to illustrating the subtle connotations of the Qur'anic words with a modern methodology based a coherent and logical conception in understanding the Qur'anic text. The theory of the context, with its outer and inner sides, is an essential foundation for the research as it uses all the tools leading to understanding and exploring the inside of the text, starting with the smallest unit of the text, the sound, passing to the minor unit, the word, and ending with the major unit, the sentence in the context of the Qur'anic text. For that reason, the theory of the context has become an integrated theory, in the full sense of the word, in the linguistics of the text. As the research aims at founding an integrated analytical approach that can be built upon when studying the one-root derivatives in the Qur'anic text, the nature and the aim of the topic require to apply the descriptive, analytical approach as a course for the study. Sometimes, however, I resort to the statistics and analyzing the results. I applied this approach in each case. I identified the contexts of the Sarkh derivatives proceeding with the linguistic analysis that starts with the lexical connotation of the root (S-R-Kh). It also includes the structural, morphological, phonetic and the phonological analysis along with the recommendations. Among the conclusions reached by the study is that the three-letter root of the word S-R-Kh is based on its objective reality regarding the meaning of sound in an absolute sense and crying out in a specific sense. Its variant derivatives indicate two opposite meanings: helping and seeking help. The two meanings are not free from the connotation of crying out in their different contexts. The context of the situations and their ambience in the four positions are not free from the connotation of panic, awe, terrifying, warning and threat covered with fear and anxiety.
Keywords: القرآن الكريم -- علم الدلالة -- البلاغة القرآنية -- علم الأصوات